2016
DOI: 10.1007/s13277-016-5065-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exosomal miR-21 and miR-181a differentiates follicular from papillary thyroid cancer

Abstract: Thyroid cancer (TC) is the most common endocrine malignancy and its incidence has increased over the last few decades. As has been revealed by a number of studies, TC tissue's micro-RNA (miRNA) profile may reflect histological features and the clinical behavior of tumor. However, alteration of the miRNA profile of plasma exosomes associated with TC development has to date not been explored. We isolated exosomes from plasma and assayed their characteristics using laser diffraction particle size analysis, atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 45 publications
1
67
0
8
Order By: Relevance
“…For example, miRNAs are differentially expressed in various types of cancers and possess good diagnostic value in cancer screening [2628]. In some cases, circulating cell-free DNAs (cfDNAs) are also dysregulated in the plasma and serum of cancer patients [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miRNAs are differentially expressed in various types of cancers and possess good diagnostic value in cancer screening [2628]. In some cases, circulating cell-free DNAs (cfDNAs) are also dysregulated in the plasma and serum of cancer patients [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…23 Samsonov et al demonstrated that miR-145 restrained papillary thyroid cancer cell reproduction by targeting DUSP6. 24 However, there are fewer studies on the relationship between DUSP6 and miR-122-5p and their underlying mechanism on GC.…”
Section: Introductionmentioning
confidence: 99%
“…Up-regulation of miR-21 is implicated in cancer progression and metastasis (22,23). Several studies indicate that miR-21 expression is associated with the progression and recurrence of thyroid carcinomas (24)(25)(26). We showed that miR-21 is a direct target of OTUD6B-AS1.…”
Section: Discussionmentioning
confidence: 69%